Religious moderation as an effort to prevent conflict based on religious beliefs of the bonokeling community - Lendra Yuspi (Jurnal Scientia, 2024)
In the midst of the diversity of religious beliefs that exist in society, faith-based conflicts often become a tapering problem. It is not uncommon to see conflicts arising from religious beliefs at various levels. The Bonokeling indigenous community is known as a community that firmly maintains traditions, which can trigger conflict. Based on this background, an understanding of the social relations of the Bonokeling community, namely: 1) the relationship among adherents and 2) the relationship with other communities, as well as an understanding of religious moderation in order to anticipate conflicts based on religious beliefs in the community of Pekuncen Village, Jatilawang District, Banyumas Regency, is important to do. The research method used is qualitative research. The research uses a mixed paradigm, namely the paradigm of social facts, social definitions; and social behavior. The analysis technique used is interactive model analysis. The results of the study found that: 1), the social relationship of Bonokeling followers with fellow Bonokeling followers is good with no problems, then the social relationship of Bonokeling followers with other communities, namely with adherents of Islam and others is also good with no problems. 2), religious moderation is a strong and relevant solution in anticipating religious belief-based conflicts. 3), anticipating conflicts based on religious beliefs in society is absolutely necessary. With an inclusive, dialogical, and patient approach, society can build cohesion and unity, while still upholding individual religious freedom. Religious moderation is not just a theoretical concept, but a practice that has a positive impact in creating a harmonious and peaceful society.